Strategi Manajemen Kelas untuk Meningkatkan Prestasi Belajar Siswa - Masfufah Masfufah; Didit Darmawan; Eli Masnawati (Universitas Katolik Widya Karya Malang, 2023)
Classroom management is a strategic approach that plays a central role in improving student learning achievement in educational settings. The main objective of this study was to investigate the effectiveness of classroom management to improve student learning outcomes. This research adopts a type of field research with a qualitative naturalistic approach, which was chosen based on the consideration that the focus of the research is on data that is able to provide a picture and painting of complex social realities into concreteness. The main source of information and data in this study involved interviews with homeroom teachers, school principals and students. The results show that every decision and strategy taken by teachers not only creates a physical space in the classroom, but more deeply, forms the basis of character and understanding. In a well-managed classroom, the expected conditions are created. The teacher serves not only as a leader, but also as a harmonizer who creates harmony among the diverse personalities and talents of students. Through wisdom and sensitivity to classroom dynamics, teachers are able to create an environment that fosters a sense of security, curiosity and passion for learning. Effective classroom management gives each student the opportunity to develop according to his or her potential. They are not only invited to participate, but also to collaborate and immerse themselves in the learning process. In a well-organized classroom setting, chaos can turn into cooperation, challenges into opportunities for growth, and uncertainty into confidence in one's abilities.